Non-suicidal self-injury and suicidal ideation among adolescents: the chain-mediating role of rumination and decentering - Zheng, Yinwei; Wang, Jing; Jiang, Qin; Liao, Meiling; Huang, Fajie (Frontiers in Psychiatry, 2023)
Objective To explore the relationship between non-suicidal self-injury and suicidal ideation in adolescents and examine the roles of rumination and decentering in that relationship. Method By means of a questionnaire, 175 adolescent patients in a psychiatric hospital in Fujian Province were given the Functional Assessment of Self-Mutilation: Chinese Version, Positive and Negative Suicide Ideation, Ruminative Response Scale: Chinese Version, and Experiences Questionnaire: Decentering Scale. Results (1) Adolescent non-suicidal self-injury was significantly positively related to suicidal ideation and rumination and significantly negatively related to decentering. Suicidal ideation was significantly positively related to rumination and significantly negatively related to decentering. Rumination was significantly negatively related to decentering. (2) Rumination and decentering played a complete chain-mediating role between non-suicidal self-injury and suicidal ideation. Non-suicidal self-injury was found to indirectly affect suicidal ideation along three pathways: the independent mediating role of rumination (the mediating effect accounted for 40.166%), independent mediating role of decentering (the mediating effect accounted for 41.274%), and chain-mediating role of rumination and decentering (the mediating effect accounted for 14.958%). Conclusion Adolescent non-suicidal self-injury can indirectly affect suicidal ideation through rumination and decentering. In the future, mindfulness and other methods should be used to improve individuals’ levels of decentering and cultivate emotional regulation abilities, so as to reduce the incidence of non-suicidal self-injury and suicide in adolescents.